QUELQUES EXEMPLES DE FORUMS DE DISCUSSION POUVANT INTÉRESSER LES LECTEURS DE SPORE - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
alt.agriculture.fruit } alt.agriculture.misc } alt=alternatif alt.sustainable.agriculture }bionet.agroforestry } bionet.biology.tropical } bionet=sciences biologiques bionet.parasitology }sci.agriculture sci=sciences